Adult men suicide: a developmental approach - Michel Tousignant; Monique Séguin; Gustavo Turecki; Nadia Chawky; Claude Vanier; Raymond Morissette; Alain Lesage (Journal of Men's Health, 2022)
Background and objective: This study aims to verify the role of humiliating events and their context in provoking suicide and the contribution of childhood parental maltreatment. Materials and methods: A family member of consecutive adult male suicides, aged between 18 and 53, was recruited at the Montreal coroner’s mortuary for a psychosocial autopsy interview (N = 63) and 7 others through the coroner-in-chief’s office. Live events were assessed with the Life Events and Difficulties Schedule (LEDS) and parental maltreatment with the Child Experience of Care and Abuse (CECA) Interview. Results: Two thirds of the suicides presented most of the following factors: a separation from a partner, half of them involving the man’s intractable behavior, financial and marital difficulties, a diagnosis of substance use and/or personality disorder, a history of parental maltreatment and impulsivity. However, other subgroups of men suicide differed significantly from this portrait. Conclusions: Humiliation events and parental maltreatment are key factors of men’s suicide.